Methylone is a rapid-acting neuroplastogen with less off-target activity than MDMA - Warner-Schmidt, Jennifer; Stogniew, Martin; Mandell, Blake; Rowland, R. Scott; Schmidt, Eric F.; Kelmendi, Benjamin (Frontiers in Neuroscience, 2024)
Background: Post-traumatic stress disorder (PTSD) is a highly prevalent psychiatric disorder that can become chronic and debilitating when left untreated. Available pharmacotherapies are limited, take weeks to show modest benefit and remain ineffective for up to 40% of patients. Methylone is currently in clinical development for the treatment of PTSD. Preclinical studies show rapid, robust and long-lasting antidepressant-like and anxiolytic effects. The mechanism of action underlying these effects is not yet fully understood. This study investigated the downstream gene expression changes and signaling pathways affected by methylone in key brain areas linked to PTSD and MDD. It also sought to determine whether neuroplasticity-related genes were involved. We compared effects of methylone with MDMA to explore similarities and differences in their brain effects because MDMA-assisted psychotherapy has recently shown benefit in clinical trials for PTSD and methylone is a structural analog of MDMA. Methods: Monoamine binding, uptake and release studies were performed and a high-throughput-screen evaluated agonist/antagonist activities at 168 GPCRs in vitro. We used RNA sequencing (RNAseq) to probe drug-induced gene expression changes in the amygdala and frontal cortex, two brain areas responsible for emotional learning that are affected by PTSD and MDD. Rats were treated with methylone or MDMA (both 10 mg/kg, IP), and their responses were compared with controls. We performed functional enrichment analysis to identify which pathways were regulated by methylone and/or MDMA. We confirmed changes in gene expression using immunohistochemistry. Results: Methylone, a monoamine uptake inhibitor and releaser, demonstrated no off-target effects at 168 GPCRs, unlike MDMA, which showed activity at 5HT2A and 5HT2C receptors. RNA-seq results revealed significant regulation of myelin-related genes in the amygdala, confirmed by immunohistochemistry. In the frontal cortex, methylone significantly upregulated genes implicated in neuroplasticity. Conclusions: Results suggest that (1) methylone is a rapid-acting neuroplastogen that affects key brain substrates for PTSD and MDD and that (2) methylone appears to exhibit higher specificity and fewer off-target effects than MDMA. Together, these results are consistent with the reported clinical experiences of methylone and MDMA and bolster the potential use of methylone in the treatment of PTSD and, potentially, other neuropsychiatric disorders.